Pengaruh Metode KWL (Know, Want, Learned) Berbantuan Media Kartu Kata terhadap Keterampilan Membaca Pemahaman Siswa Kelas IV di Sekolah Dasar - Rita Septiana; Muhammad Tahir; Lalu Wira Zain Amrullah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the effect of the KWL (Know, Want, Learned) method assisted by word card media on the reading comprehension skills of fourth-grade elementary school students. This research is a quantitative study using a Quasi-Experimental approach with a Nonequivalent Control Group design. The research subjects consisted of 60 fourth-grade students from SDN 34 Ampenan and SDN 12 Ampenan. Data collection techniques were conducted through reading comprehension skill tests and observation sheets to measure the implementation of learning. The obtained data were analyzed using inferential statistical tests, namely normality and homogeneity tests, which indicated that the data were normal and homogeneous, as well as the Independent Sample T-test. The results show that there is a significant difference after the KWL method assisted by word card media was applied. This is indicated by the higher average posttest score of the experimental class compared to the control class, as well as the T-test results conducted at a 5% significance level, which obtained a sig (two-sided p) value of 0.001 < 0.05, indicating a significant difference. Thus, it can be concluded that the KWL method assisted by word card media influences the reading comprehension skills of fourth-grade elementary school students.